Influence of Mixed Sludge on the Operation of Coal-fired Unit Boiler. Issue 2 (May 2021) - Zhang, Limeng; Dong, Xinguang; Zhao, Zhonghua; Liu, Jinglong; Wang, Haichao; Zhang, Xuhui; Liu, Ke; Hou, Fanjun
Abstract: In this paper, the operation characteristics of a 480t/h ultra-high pressure pulverized coal fired boiler with municipal sludge were studied. The results show that: mixing sludge has a negative impact on the thermal efficiency of boiler operation, and with the decrease of boiler evaporation and the increase of sludge mixing ratio, the decline of boiler thermal efficiency increases, but mixing sludge can effectively reduce the emissions of nitrogen oxides and sulfur dioxide in the boiler. Through the optimization and adjustment test, it is found that the optimal oxygen content of the boiler is 3.61% when the proportion of sludge is 5%.